Application of potassium nitrate to increase flower and seeds formation on different shallots varieties. Issue 1 (April 2021) - Bakri, A; Syam'un, E; Musa, Y; Ulfa, F
Abstract: The use of True Shallot Seeds (TSS) as an alternative planting material to produce quality shallots ( Allium cepa L.), is constrained by the low formed of flowers and seeds. This study investigates the effect of potassium nitrate (KNO3) concentration on the flower and seeds formation of three shallots cultivars, and was conducted from September 2019 to January 2020 in District of West Sinjai, Sinjai Regency, South Sulawesi, at 1250 m above sea level. The experiments was set up as split plots design and provided with 3 replications. The main plot was shallots varieties (Sanren, Superpilip, and Tajuk) and the subplot was PN dosage (0, 7, 9, and 11 g per plant). Experimental results revealed that interaction of PN and shallots varieties gave a significant effect onthe average number of flower buds, number of filled flower capsules, and seeds weight. Application of 11 g PN on Superpilip varieties was able to produce the highest average number of flower buds (63), number of filled flower capsules (66.62), and seed weight (4.4 grams). This finding concludes that application of 11 g potassium nitrate per plantinduce flowering and increase seeds production of shallots, however the results will vary depend on the varieties.